ASUPAN KALSIUM DAN VITAMIN C DENGAN TINGGI BADAN SISWA SD NEGERI INPRES BERU-BERU KECAMATAN KALUKKU KABUPATEN MAMUJU - Hapzah Hapzah; Supriandi Supriandi (Jurnal Kesehatan Manarang, 2016)
The Primary School Children is a strategic objective to improve nutrition in the community because at this time the development of the child begins to form steady. The problem of stunting or short children can be affected by the lack of various nutrients, inadequate intake of nutrients such as protein, calcium and others will be at risk of child stunting or short. This type of research is descriptive. The sample in this study are as many as 65 people were obtained by purposive sampling. The intake of calcium and vitamin C taken with the formulir recall 24 hours, and the height was measured with use the microtoice. The results showed that there were 76.9% short of nutritional status (stunting) indicator of TB/U, there are 100% of children who have a calcium intake of less, and 96.9% were vitamin C intake less.